Dampak adopsi teknologi jajar legowo terhadap produksi padi sawah di Kabupaten Bombana - Rusdin Rusdin; Bahari Bahari; Idrus Salam (Jurnal Sosio Agribisnis, 2023)
One effort to increase the production and productivity of lowland rice in Bombana Regency is the "Gerakan Peningkatan Produktivitas Padi pada Sawah Irigasi (GP3SI)" program, namely by adopting jajar legowo super technology. This research aims to analyze the impact of adopting jajar legowo super technology on lowland rice production. The research was carried out in Lameroro Village, Rumbia District, and Lokomea Village, Rarowatu District, Bombana Regency, in July–December 2021. Sample selection used the cluster random sampling method. The total sample was 80 farmers. The data collected consists of: land area, number of seeds, labor, NPK fertilizer, urea fertilizer, and the amount of pesticides/herbicides used in rice farming, as well as production. Data analysis was carried out using the Cobb-Douglas production function model. The research results show that together, the variables land area (X1), labor (X2), seeds (X3), NPK fertilizer (X4), urea fertilizer (X5), pesticides (X6) and dummy variables have a significant effect on rice production. rice fields (Y). Partially, the production factor is land area; total manpower; seed; pesticides and dummy variables (adoption of Jajar Legowo Super technology) have a significant effect on lowland rice production. Meanwhile, NPK fertilizer; and urea fertilizer has no significant effect on lowland rice production in Bombana Regency. The adoption of Jajar Legowo technology has had an impact on increasing lowland rice production. Keywords: factors of production; rice; jajar legowo super